Melissabot: An agro-climatic information chatbot system for Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Melissabot was implemented in Telegram and Facebook Messenger social networks. Chatbot responses were evaluated by different users, in terms of accuracy and usefulness of the information, who found the use of this type of tool as an adequate source of consultation of climate information and crop production for decision-making.